Gestión de tesorería en el Gobierno Autónomo Descentralizado Parroquial Rural de San Juan en el año 2023. - Espinoza Chila, Lady Dajanna (2024)
The present degree work referring to treasury management in the San Juan Rural Parochial Decentralized Autonomous Government in the year 2023, several challenges are evident, of which is the limitation of resources, which makes the implementation of health development programs difficult. treasury and retention of qualified personnel. Due to deficiencies in specialization in human resources, little selection processes are generated and the inability to identify and develop the potential of employees, on the other hand, the absence of access to training and training opportunities limits the professional growth of staff. Internal communication can challenge due to the hierarchical structure, which sometimes hinders the flow of information, for roles and responsibilities in a parish environment can make effective identification and management difficult, which can affect staff motivation and their commitment to institutional goals and overcoming these challenges in treasury management requires solutions adapted to the specific context of the organization.